Essential Oil Composition and Antibacterial Activity of Colubrina Asiatica (L.) Brong - Desai, Nivas; Gaikwad, D. K. (Asian Journal of Pharmaceutical Research and Development, 2014)
The essential oil obtained from the fresh leaves of Colubrina asiatica (L.) Brong. by hydrodistillation was analysed by gas chromatography and gas chromatography-mass spectro metry. The essential oil content quantified showed presence of 10 compounds in which, dodecamethylcyclohexasiloxane has showed the highest (17%) and Dehydro-N-[4,5-methylenedioxy2-nitrobenzylidene]-tyramine showed the lowest percentage (1.9%).α-cubebene, comprised of 14% .The in vitro antimicrobial activity of the leaf oil was studied by MIC technique. The leaf essential oil was tested against both Grampositive and Gram-negative bacterial strains. Antibacterial activity was significant against Gram positive bacterium, Staphylococcus aureus.